China's New Private Education Law - Yan, Fengqiao; Levy, Daniel (International Higher Education, 2003)
The private education law, promulgated on December 28, 2002, is China’s first national legislation on private education. The law covers all educational levels, although we are focusing on the three articles (16, 53, and 55) that cover higher education. The law’s main thrust concerning higher education is to provide a legal framework to facilitate private growth and initiate a longer process to accredit, merge, dismantle, and change institutions at that level.